Effects of Topical Gabapentin on Ocular Pain and Tear Secretion - Maurizio Cammalleri; Rosario Amato; Melania Olivieri; Salvatore Pezzino; Paola Bagnoli; Massimo Dal Monte; Dario Rusciano (Frontiers Media S.A., 2021)
Neuropathic ocular pain is a frequent occurrence in medium to severe dry eye disease (DED). Only palliative treatments, such as lubricants and anti-inflammatory drugs, are available to alleviate patients' discomfort. Anesthetic drugs are not indicated, because they may interfere with the neural feedback between the cornea and the lacrimal gland, impairing tear production and lacrimation. Gabapentin (GBT) is a structural analog of gamma-amino butyric acid that has been used by systemic administration to provide pain relief in glaucomatous patients. We have already shown in a rabbit model system that its topic administration as eye drops has anti-inflammatory properties. We now present data on rabbits' eyes showing that indeed GBT given topically as eye drops has analgesic but not anesthetic effects. Therefore, opposite to an anesthetic drug such as oxybuprocaine, GBT does not decrease lacrimation, but-unexpectedly-even stimulates it, apparently through the upregulation of acetylcholine and norepinephrine, and by induction of aquaporin 5 (AQP5) expression in the lacrimal gland. Moreover, data obtained in vitro on a primary human corneal epithelial cell line also show direct induction of AQP5 by GBT. This suggests that corneal cells might also contribute to the lacrimal stimulation promoted by GBT and participate with lacrimal glands in the restoration of the tear film, thus reducing friction on the ocular surface, which is a known trigger of ocular pain. In conclusion, GBT is endowed with analgesic, anti-inflammatory and secretagogue properties, all useful to treat neuropathic pain of the ocular surface, especially in case of DED.